Resepsi Estetik Jauss terhadap Ayat-Ayat Jilbab: Studi Komparatif Sastra Tafsir Kemenag VS. Narasi Hijab Fashion di TikTok - Davin Zachary Yasa; Siti Hanifah Amaliah; Zahira Sufyan; Zahra Mawaddah; Tenny Sudjatnika (Indo Publishing, 2026)
The hijab phenomenon in Indonesia has undergone a radical transformation from a static theological signifier to a dynamic visual commodity in the digital era. This research aims to analyze the shift in religious authority and the interpretation of hijab verses (Surah Al-Ahzab: 59 and Surah An-Nur: 31) by comparing the official narrative of the Ministry of Religious Affairs (Kemenag) and the hijab fashion narratives on TikTok. Using Hans Robert Jauss’s Aesthetic of Reception theory, specifically the concepts of